2012
DOI: 10.1007/s11695-012-0806-x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea: Is Routine Preoperative Screening Necessary?

Abstract: Sleep apnea screening prior to bariatric surgery identifies an additional 25 % of patients as having OSA. In this study, unscreened morbidly obese patients did not have an increased incidence of cardiopulmonary complications after surgery compared to screened patients. Prospective randomized studies should be conducted to definitively assess utility and cost effectiveness of routine OSA screening of all morbidly obese patients undergoing surgery. Preoperative OSA screening may be safely omitted when randomizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Of the included risk prediction models, only DeMaria et al tested all their patients with polysomnography prior to surgery. However, the need for testing preoperatively is heavily debated by some authors [47]. Some significant predictors were absent in our validation cohort, like BMI >70 (LABS), a dependent or impaired functional status (LABS, Gupta et al and Maciejewski et al), age ≥65 years (Maciejewski et al), and ASA class 4/5 (Maciejewski et al).…”
Section: Resultsmentioning
confidence: 81%
“…Of the included risk prediction models, only DeMaria et al tested all their patients with polysomnography prior to surgery. However, the need for testing preoperatively is heavily debated by some authors [47]. Some significant predictors were absent in our validation cohort, like BMI >70 (LABS), a dependent or impaired functional status (LABS, Gupta et al and Maciejewski et al), age ≥65 years (Maciejewski et al), and ASA class 4/5 (Maciejewski et al).…”
Section: Resultsmentioning
confidence: 81%
“…No observational evidence directly addressing the question was found. Meta-analysis of observational studies suggested that patients with obstructive sleep apnea or related disorders were more likely to sustain atrial fibrillation (OR 1.51, 95% CI 1.36 to 1.69) or hypoxemia (WMD − 3.8%, 95% CI − 5.4% to − 2.2%) [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. The latter outcome might not be clinically important, whereas the summary certainty in the evidence was very low due to risk of bias (non-controlled confounders in cohort studies), imprecision, statistical and conceptual heterogeneity (differences in definition of sleep apnea and method of diagnosis) (Supplementary Table 6).…”
Section: Justificationmentioning
confidence: 99%
“…Adequate control of previously identified comorbidity like hypertension and diabetes mellitus and undiagnosed obesity related pathology such as obstructive sleep apnea (OSA) must be excluded. This is not uncommon as was demonstrated by Nepomnayshy et al in a study of 882 morbidly obese patients screened for sleep apnea prior to bariatric surgery, where they identified an additional 25 percent of patients with OSA [16]. Obese patients should be evaluated for predictors of both difficult mask ventilation and difficult intubation, as additional equipment and skilled personnel should be readily available if necessary.…”
Section: Anaesthetic Assessmentmentioning
confidence: 93%